The relationship between women’s body mass index and breast cancer outcomes was U-shaped - Wei, Wensong; Wei, Suosu; Huang, Zhen; Zhang, Qiuhuan; Liu, Fei; Xie, Yujie; Wei, Jing; Mo, Chongde; Zhou, Ying; Qin, Shengpeng; Zou, Quanqing; Yang, Jianrong (Frontiers in Oncology, 2023)
Background: Some studies have examined the possibility that being overweight is associated with the outcomes of breast cancer (BC). However, this remains unclear due to the limitations of clinical data. The objective of this cohort research was to examine the Correlation between body mass index (BMI) and BC prognosis. Methods: From March 7,2013to December 31,2019,1049breast cancer victims in China participated in this retrospective cohort research. Using Kaplan-Meier curves, multivariate Cox proportional models, and restricted cubic spline (RCS) analysis, the association between BMI and overall survival (OS) and breast cancer-specific survival (BCSS) was analyzed. Results: During the follow-up period after BC diagnosis (median 4.87 years, interquartile range 3.26-6.84 years),71BC patients （6.77%） died, of which 50（70.42%） were attributed to BC. After controlling for clinical variables and other confounders, RCS analysis revealed a U- shaped U-shaped relationship between BMI levels and OS and BCSS. When the patient's BMI was roughly 23 kg/m2, the U-shaped curves reached their lowest points. The Kaplan-Meier curves and the multivariate Cox regression analysis produced findings that were congruent with those produced by the RCS studies. Conclusion: According to the findings of our research, BMI is a significant independent prognostic factor for BC, and the relationship between BMI and OS and BCSS was U-shaped. This suggests that intervention in patients 'BMI can improve patient outcomes.